An Anti-Tissue Factor Monoclonal Antibody which Inhibits TF Vlla Complex Is a Potent Anticoagulant in Plasma - Ruf, Wolfram; Edgington, Thomas S (Thrombosis and Haemostasis, 1991)
Tissue factor (TF) functions as the receptor and cofactor for factor VIIa (VIIa) to form a proteolytically active TFVIIa complex on cell surfaces. We here demonstrate that most MAbs against human TF were poor inhibitors of TF function in plasma and that they inhibited preformed TF-VIIa complex at a slow rate which was dependent on dissociation of VIIa from the cell surface TF. An exception was defined by one MAb (TF8-5G9) which was an effective immediate anticoagulant in plasma. Binding of TF8-5G9 to TF-VIIa inhibited catalytic function prior to dissociation of the TF-VIIa complex. This analysis thus establishes two distinct mechanisms by which MAbs interfere with TF function. The MAb TF8-5G9 introduces a therapeutic principle for rapid arrest of inappropriate triggering of coagulation by TF as well as the TF-VIIa complex in vivo.